Cariogenicidade do leite materno: mito ou evidência científica - Lemos, Leticia Vargas Freire Martins [UNESP]; Correia, Marilia Ferreira [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Myaki, Silvio Issáo [UNESP]; Zuanon, Angela Cristina Cilense [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2012)
Introduction: Breast-feeding has stood out as health care measure and is part of the Government’s National Health Policy, involving dental professionals. However, it has been suggested that breast milk could be a risk factor for the development of early childhood caries. Objective: The purpose of this report was to search for scientific evidence that would support or refute the statement that breastfeeding is associated with the development of early childhood caries. Method: Medline and SciELO databases were consulted to retrieve studies, ranging from laboratory investigations to epidemiological surveys, which relate breastfeeding to dental caries. The key words ‘breast-feeding’ and ‘dental caries’ were used on the reference search. There was no scientific evidence that could demonstrate a clear relationship between breast milk and cariogenicity. This is attributed to fact that dental caries is a multifactorial disease that is susceptible to multiple confusing factors, among which the early introduction of sucrose to the infant’s diet and late introduction of oral hygiene habits. The dentist should encourage exclusive breast-feeding because, in addition to the undeniable benefits to the child’s physical and psychological health, it contributes to a harmonic facial growth and prevents the development of atypical deglutition and malocclusions, in combination with early introduction of oral hygiene habits and noncariogenic diet. Conclusion: There is no scientific evidence to demonstrate an association between breast-feeding and early childhood caries.

Introdução: A amamentação materna tem sido destacada como medida de promoção de saúde, fazendo parte da Política Nacional de Saúde, envolvendo o profissional da Odontologia, porém o leite materno tem sido sugerido como um fator de risco para o desenvolvimento da cárie precoce da infância. Objetivo: Buscar evidências científicas na literatura que comprovem ou refutem a afirmação de que o aleitamento materno está associado com a Cárie Precoce da Infância. Método: A partir da consulta das bases de dados Medline e SciELO, foram incluídos desde estudos laboratoriais a levantamentos epidemiológicos que relacionam o aleitamento materno com a presença da doença cárie. Os descritores utilizados para esta busca foram: “breast feeding” e “dental caries”. Constatou-se que não existem evidências científicas adequadas que demonstrem relação clara sobre a cariogenicidade do leite materno, em virtude da doença cárie ser multifatorial, o que a torna susceptível a presença de fatores confundidores, como por exemplo, a introdução precoce da sacarose a dieta do lactente e o início tardio de hábitos de higiene bucal. O aleitamento materno exclusivo deve ser estimulado pelo cirurgião dentista, uma vez que, além dos inegáveis benefícios para a saúde física e psicológica da criança, favorece um crescimento facial harmônico e previne o desenvolvimento de deglutição atípica e de maloclusões, em conjunto com a inserção precoce de hábitos de higiene e dieta não cariogênica. Conclusão: Não existem evidências científicas que suportem a afirmação de que o aleitamento materno está associado com a Cárie Precoce da Infância.
Human milk cariogenicity: myth or scientific evidence
Keywords: Breast feeding; Dental caries; Diet; Cariogenic; Breast feeding; Dental caries; Cariogenic